Konvergensi Media Lokal Batam TV di Era-Multiflatform Finch - Asmara, Ujang (Milenial: Journal for Teachers and Learning, 2024)
This research aims to study the convergence phenomenon of local media Batam TV in the multi-platform era. This research uses a qualitative method with a phenomenological approach. The data collection techniques used in this research are methods, observation and documentation. The data analysis technique for this research uses the Craswell phenomenological data analysis technique. Based on the results of this research, it can be concluded that the media convergence implemented by some local media, especially Batam TV, is a very appropriate step. The combination of the three elements of 3M Strategy (Multimedia, Multichannel and Multiplatform) is the first step in implementing media convergence. Continuum convergence will be achieved through (Crosspromotion, cloning, coopetition, content sharing, and full convergence). The steps that Batam TV has taken include convergence from conventional to online. This convergence itself can take the form of: collaboration between media, use of technological media for the creation or distribution of program content and so on. However, the most important thing is to remain committed to building local television that promotes local culture (Malay community).